CONTRIBUIÇÕES PARA A PRÁTICA SIGNIFICATIVA DE ENSINO DO CORPO HUMANO NA FORMAÇÃO DE PROFESSORES PEDAGOGOS - Cebulski, Gabriela (2019)
The present study is a qualitative research, of the action research modality, which aimed to elaborate a significant pedagogical proposal about the human body, that could provide contributions to the initial formation in Sciences of pedagogical teachers. Therefore, semi-structured interviews were conducted with teachers of the UNICENTRO Pedagogy course, in order to investigate possible formative gaps in the course, obtain information about the participants' view of the subject and their pedagogical practices. From the results obtained in these interviews, potentially significant material was developed in the format of a didactic guide, which approached the human body theme, based on the Theory of Meaningful Learning. This material was presented to teachers and students of the Pedagogy course by means of classes and activities, with the intention of being evaluated and improved. The students answered pre- and post-intervention structured questionnaires, which contained objective and subjective questions investigating their perceptions of the materials presented. The teachers evaluated the materials by means of a specific post-intervention questionnaire. The results obtained were analyzed by content analysis. The didactic guide obtained positive evaluations from both academics and teachers, related that the activities developed helped them to understand the physiology and anatomy of the human organism, and that the scientific concepts acquired meanings for the participants, contributing to the education in science of teachers of Pedagogy. In general, the scores given to the potentially significant material corresponded to the optimal concept, demonstrating that the material has achieved its initial goal. In the final evaluation made by the teachers, it was suggested that the guide presented a deeper understanding of the specific contents of the theme and more research sources, the suggestions were accepted and made. It is hoped that the results obtained in this study may inspire other researchers to develop cooperation and partnership work between different areas of knowledge, thus providing new horizons for Brazilian education.